Difficulties of the physical Educational Environment Facing the Teaching of Biology and Land Curriculum From the point of view of the Subject Teachers (A Field Study in basic education schools a second cycle in Lattakia city) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The current research tackles the difficulties of the physical Educational Environment Facing the Teaching of Biology and Land Curriculum From the point of view of the Subject Teachers in basic education schools a second cycle in Lattakia city,  and to study the differences in their views about the difficulties they face are attributed according to variables (sex, experience, educational qualifications). In order to achieve the objective of the research, the analytical descriptive method was used. The sample included (138) Teachers in the schools of the second cycle of basic education in Lattakia city for the academic year (2018/2019). The questionnaire consisted of four areas, which included (40) paragraph.The reached several results, the most important of which:- The difficulties of the physical Educational Environment Facing the Teaching of Biology and Land Curriculum From the point of view of the Subject Teachers in basic education schools a second cycle in Lattakia city came to a high degree.- There were no statistically significant differences between the average estimation of the members of the research sample according to the variables (sex, experience).- There are statistically significant differences between the average of the assessment of the members of the research according to the variable of scientific and educational qualification in favor of the Education Preparation Diploma Teachers.The research introduced following proposals: necessity of building new labs and supply them with modern equipment’s